On near‐wall jets in a disc‐like gas vortex unit. Issue 5 (23rd October 2016) - Niyogi, Kaustav; Torregrosa, Maria M.; Pantzali, Maria N.; Heynderickx, Geraldine J.; Marin, Guy B.; Shtern, Vladimir N.
Abstract : To clarify the three‐dimensional (3D) structure of near‐wall jets observed in disc‐like gas vortex units (GVUs), experimental and numerical studies are performed. The experimental results are obtained using stereoscopic particle image velocimetry (PIV), laser doppler anemometry, pressure probes and surface oil flow visualization techniques. The first three techniques have been used to investigate the bulk flow hydrodynamics of the vortex unit. Surface oil flow visualization is adopted to visualize streamlines near the end‐walls of the vortex unit. The surface streamlines help to determine the azimuthal and radial velocity components of the radial near‐wall jets. Simulations of the vortex unit using FLUENT ® v.14a are simultaneously performed, computationally resolving the near‐wall jet regions in the axial direction. The simulation results together with the surface oil flow visualization establish the 3D structure of the near‐wall jets in GVUs for the first time in literature. It is also conjectured that the near‐wall jets develop due to the combined effect of bulk flow acceleration and swirl. The centrifugal force diminishes in the vicinity of the end‐walls. The radially inward pressure gradient in these regions, no longer balanced by the centrifugal force, pushes gas radially inward thus developing the near‐wall jets. © 2016 The Authors AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers AIChE J, 63: 1740–1756, 2017